Lost in the Funhouse: Reflections on Teaching a Course about Reflections on Learning - Bergart, Robin; Parlette-Stewart, Melanie (Université d'Ottawa | University of Ottawa, 2018)
How can we challenge students to take a more critical view of learning, and develop their metacognitive abilities? We share our Framework-inspired semester-long course. You will try some of the reflection exercises we used and discuss the value of such exercises and their relevance to the Framework.